Exploring User Experiences of Chat GPT and Google Gemini AI : A SUS and EUCS Approach - Fausta Rizky Abriansah; Nanda Dwi Kurniawan; Praditya Rendi Ferdian; Daffa Nurin Nabil Ma'arif; Azmi Maulana Firdaus; Pratama Angga (Redtech Putra Benua, 2024)
This study evaluates user experience and satisfaction of two AI platforms, Chat GPT and Google Gemini, using the System Usability Scale (SUS) and End-User Computing Satisfaction (EUCS) approaches. The study involved 78 respondents from diverse backgrounds who provided evaluations based on five main dimensions of usability (Learnability, Efficiency, Memorability, Error, Pleasantness) and five dimensions of user satisfaction (Content, Accuracy, Format, Ease of Use, Timeliness). The results show that both platforms achieved a